The safety profiles of Nigella sativa oil as a supplement in diabetic neuropathy patients: assessment on hematology and hepatorenal functions - Syuhada; Anggadiredja, Kusnandar; Kurniati, Neng Fisheri; Akrom (Penerbit Universiti Kebangsaan Malaysia, 2025)
The potential effectiveness of Nigella sativa oil (NSO) has been shown in patients with diabetic neuropathy. However, its safety profiles in this group of patients remain underexplored. This study aimed to evaluate the hematological and biochemical safety profiles of NSO in this population. A single-center clinical trial was conducted involving 24 patients with diabetic neuropathy who received NSO at a dose of 2 mL/day for 30 days. Hematological and biochemical parameters were assessed before and after intervention. The hematological parameters included hemoglobin (HGB), white blood cell (WBC) count, red blood cell (RBC) count, hematocrit (Hct), and platelet (Plt) count. Meanwhile, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatinine were measured representing hepatorenal parameters. Other adverse events accompanying NSO supplementation were also recorded. The results showed no significant changes in hematological parameters or hepatorenal function markers. A slight increase in mean corpuscular hemoglobin concentration (p = 0.0483) was observed, but values remained within normal physiological limits. Other adverse events reported were categorized non-serious, except one transient case of tachycardia that resolved without clinical consequences. The findings suggest that NSO is safe for patients with diabetic neuropathy. Further long-term studies with larger sample sizes are recommended to confirm these results.